2018
DOI: 10.1016/s2468-2667(18)30075-6
|View full text |Cite
|
Sign up to set email alerts
|

A needs-based workforce model to deliver tertiary-level community mental health care for distressed infants, children, and adolescents in South Australia: a mixed-methods study

Abstract: National Health and Medical Research Council (Australia), Department of Health SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
(31 reference statements)
1
31
0
Order By: Relevance
“…Most of these programmes offer a limited amount of free or subsidised treatment sessions, which may not be sufficient for children and adolescents with more complex treatment needs; this might, in part, explain why cost for those with a partially met need remained one of the most important barriers at both time points. These findings may also support recent estimates that a fivefold increase in community-based state-funded child and adolescent services is needed to meet current clinical need in Australia (Segal et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Most of these programmes offer a limited amount of free or subsidised treatment sessions, which may not be sufficient for children and adolescents with more complex treatment needs; this might, in part, explain why cost for those with a partially met need remained one of the most important barriers at both time points. These findings may also support recent estimates that a fivefold increase in community-based state-funded child and adolescent services is needed to meet current clinical need in Australia (Segal et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…For pediatricians, primary care physicians, psychiatrists, and other clinicians working with children and adolescents, the need to be alert to the maltreating family context when seeing emotional and behavioral problems is reinforced. 12 Other research by the lead author 34 found that mental health services in SA are grossly inadequate to support the mental health of infants, children, adolescents, and their families. In this mortality study, we highlight the tragic consequences of this gap.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Factors contributing to the high prevalence of mental illness in regional settings are believed to be largely socioeconomic in origin, including unemployment/low household income, social isolation, low educational attainment, and limited physical/financial access to health services (Handley, Rich, Lewin, & Kelly, 2019; Sengupta & Benjamin, 2015). With this in mind, while increased access to evidence‐based therapies is integral to improving health outcomes in regional populations living with mental/behavioural disorders (Asarnow, Rozenman, Wiblin, & Zeltzer, 2015), so must be the provision of appropriate psychosocial services and preventive measures (Dreger, Buck, & Bolte, 2014; Furber, Segal, Leach, & Guy, 2017; Furber et al., 2015; Segal et al., 2018).…”
Section: Discussionmentioning
confidence: 99%